Pengujian Efektivitas dan Kemudahan Penggunaan Financial Technology Terhadap Kinerja UMKM - Angga Kurniawan; Suyanto Suyanto; Rizqy Anisa Nuraini (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This study was objected to analyze the influence of Effectiveness, and Ease of Using Financial Technology on the Performance of Micro, Small and Medium Enterprises Study on Go-pay Merchants in Metro City. The population in this study was 65 respondents. The sampling technique in this study was Purposive Sampling Technique. Data analysis in this study used SPSS version 22 through multiple linear tests. The results of this study outcame that effectiveness partially or simultaneously influences the performance of micro, small and medium enterprises in the study of Go-pay Marchants in Metro City. But the ease of using Financial Technology did not significantly influence the performance of Micro, Small and Medium Enterprises